Accelerated testing method to estimate the long‐term hydrostatic strength of semi‐crystalline plastic pipes. Issue 5 (5th March 2019) - Taherzadehboroujeni, Mehrzad; Kalhor, Roozbeh; Fahs, Gregory B.; Moore, Robert B.; Case, Scott W.
Abstract : The ability to quickly develop predictions of the service lifetime of plastic pipes at different load levels allows designers to choose the best plastic material and design pipe for a specific application. Additionally, it helps material producers to rapidly design, manufacture, test, screen, and modify the base polymeric material. The aim of this study is to introduce a combined experimental and analytical framework to develop accelerated lifetime estimates for semi‐crystalline plastic pipes which is sensitive to the structure, orientation, and morphology changes introduced by changing processing conditions. To accomplish this task, high density polyethylene (HDPE) is chosen as the exemplary base material and custom fixtures are developed to admit tensile and hoop burst tests on the as‐manufactured HDPE pipes. A pressure‐modified Eyring flow equation is employed to predict the rupture lifetime of HDPE pipes using the measured mechanical properties under uniaxial tensile and compression loading in different temperatures and strain rates. The method allows the prediction of pipe service lifetimes in excess of 50 years using experiments conducted over approximately 10 days instead of the traditional 13 months. POLYM. ENG. SCI., 60:879–888, 2020. © 2019 Society of Plastics Engineers